1996
DOI: 10.1093/oxfordjournals.eurheartj.a014963
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the right ventricle in valvular heart disease

Abstract: The importance of the right ventricle as a determinant of clinical symptoms, exercise capacity, peri-operative survival and postoperative outcome has been underestimated for a long time. Right ventricular ejection fraction has been used as a measure of right ventricular function but has been found to be dependent on loading conditions, ventricular interaction as well as on myocardial structure. Altered left ventricular function in patients with valvular disease influences right ventricular performance mainly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
71
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 52 publications
5
71
0
1
Order By: Relevance
“…RV long axis function correlated closely with the estimated radionuclide ejection fraction, as well as with the right-sided pressures. This is in accordance with previous reports describing afterload dependence of the RV systolic function, mostly represented by ejection fraction [36][37][38]. Although the myocardial deformation rate and ejection fraction are two different measurements, the current study shows a significant correlation between the peak systolic SR and the RV ejection fraction.…”
Section: Right Ventricular Function By Tissue/strain Dopplersupporting
confidence: 93%
“…RV long axis function correlated closely with the estimated radionuclide ejection fraction, as well as with the right-sided pressures. This is in accordance with previous reports describing afterload dependence of the RV systolic function, mostly represented by ejection fraction [36][37][38]. Although the myocardial deformation rate and ejection fraction are two different measurements, the current study shows a significant correlation between the peak systolic SR and the RV ejection fraction.…”
Section: Right Ventricular Function By Tissue/strain Dopplersupporting
confidence: 93%
“…[1][2][3][4][5] Survival in pulmonary hypertension (PH) patients depends on the capability of the RV to adapt to chronically elevated pulmonary artery pressures. 6 Therefore, an accurate evaluation of RV pump function is crucial for screening, diagnosis, and follow-up assessment in PH.…”
mentioning
confidence: 99%
“…11 Exercise-induced changes in radionuclide RV ejection fraction seemed to be inversely related to pulmonary artery pressure changes in patients with valvular left heart disease. 3 The objectives of this study were to prospectively assess exercise-induced increase in pulmonary arterial systolic pressure (PASP) as a possible measure of the RV contractile reserve using exercise stress echocardiography in patients with invasively confirmed manifest PH and to analyze the prognostic impact of exercise-induced PASP increase in context with other prognostically relevant parameters.…”
mentioning
confidence: 99%
“…Our study has demonstrated that RV Tei index is a feasible approach to estimate RV function in dogs and is not influenced by heart rate, body weight, and aging. Right ventricular (RV) function plays an important role in determining cardiac output and functional capacity in humans [1,28]. RV dysfunction has been observed in various cardiac disorders such as pulmonary hypertension (PH) [17,37], idiopathic dilated cardiomyopathy (DCM) [22], and heart failure [7,8,27].…”
mentioning
confidence: 99%